Assessment of immediate postoperative complications in patients undergoing elective laparoscopic cholecystectomy for symptomatic cholelithiasis with pre-existing co-morbid conditions - Arora, Jainendra K.; Kumar, Deepak (International Surgery Journal, 2021)
Background: Elective laparoscopic cholecystectomy done by experienced surgeon continues to be a vary safe operation however from surgical point of view, presence of co-existing clinical conditions offer independent complication risk but the influence of these clinical conditions such , diabetes, hypertension, respiratory etc. has not been emphasized enough. This study is an effort to determine the influence of co-existing clinical conditions on morbidity and mortality following laparoscopic cholecystectomy. Methods: This prospective observational study was conducted over a period of 1.8 years from August 2017 to April 2019. On the basis of selection criteria patients with symptomatic cholelithiasis were divided into two groups cases and control group. The evaluation of morbidity was done in terms of any wound infection, chest infection, cardiac complications, cholangitis, deep vein thrombosis, septicemia, etc. Results: Distribution of complications was comparable between cases and controls. (Nil: 90% versus 92.50% respectively. Proportion of patients with complications was significantly lower in patients without history of previous attack as compared to with history of previous attack. Distribution of complications were comparable between diabetic and non-diabetic. Conclusions: The presence of co- morbid conditions in the form of diabetes mellitus and hypertension does not in-crease the risk of immediate post operative complications. However, history of previous attack of acute cholecystitis can increased chances of intra-operative adhesions around calots triangle prolonging the duration of surgery which in turn can increase the risk of post operative complications.